High-performance voltammetric sensor for dichlorophenol based on β-cyclodextrin functionalized boron-doped graphene composite aerogels. (21st February 2019) - Xie, Yu; Tu, Xiaolong; Ma, Xue; Fang, Qingwen; Lu, Limin; Yu, Yongfang; Liu, Guangbin; Liu, Changxiang
Abstract: 2, 2-methylenebis (4-chlorophenol) (dichlorophenol, Dcp) is a priority pollutant that poses a serious health threat to the public. Thus, the sensitive analysis of Dcp is of great significance. Heteroatom-doped carbon nanomaterials modified electrodes have been proven to be good electrocatalysts for electrochemical sensing application. β -cyclodextrin ( β -CD) as a signal amplifier has also been utilized in biosensors. Inspired by these, in this study, a new composite of β -CD and three-dimensional (3D) boron-doped graphene aerogels (BGAs/ β -CD) has been designed as a high-performance electrochemical sensing platform for Dcp determination. Graphene aerogels possess high specific surface area, large pore volume and good conductivity, which ensure rapid mass transfer and accelerated electron transfer. Besides, boron doping causes uneven charge distribution on the graphene lattice surface, producing a large amount of flowing π electrons, which provide abundant active sites for the catalytic oxidation reaction of Dcp. In addition, Dcp molecules could be captured into β -CD through host-guest recognition, which can effectively amplify the detection signal. Combining the merits of BGAs and β -CD, the BGAs/ β -CD based sensor achieved sensitive detection of Dcp. Under optimized experimental conditions, the oxidation currents and the concentration of Dcp had a good linear relationship within 1.0 nM ∼ 21 μ M. The detection limit was estimated as 0.33 nM (S/N = 3). This study might provide a new basis for the fabrication of 3D BG-based aerogel architectural material and its application in Dcp detection.